ASSESSMENT OF ASYMPTOMATIC URINARY TRACT INFECTIONS IN UROLITHIASIS - Dr. Shanjeev K.M.; Dr. Roshan V Shetty; Dr. Anokha Jagadish; Dr. Adithya Marla (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: Genetic, metabolic, environmental, viral, socioeconomic, and nutritional factors are the multifactorial etiopathogenesis of urolithiasis, a disorder marked by the development of stones in the kidney, bladder, ureter or urethra. There is enough evidence that urolithiasis makes a substantial contribution to UTI incidence. AIMS & OBJECTIVES: To determine the proportion of UTI (symptomatic and asymptomatic), to determine the most typical organism involved in causing Urinary Tract Infections, to determine the antibiotic susceptibility of the organisms causing Urinary Tract Infections, and to study the relationship of type and duration amongst symptomatic and asymptomatic urinary tract infection in patients with urolithiasis. METHODS: This was a hospital based cross-sectional study of 152 patients, diagnosed radiologically to have urolithiasis who met the inclusion criteria. Clinical History of patients who have been diagnosed to have urolithiasis radiologically (i.e. USG or CT-KUB) was taken. Urine routine and urine culture were done to test for culture and sensitivity. RESULTS: Compared to the other group, subjects under 40 years old had a low infection rate. Urine cannot move easily when stones and other causes such as BPH, prolapse, stricture, etc., cause urinary tract obstruction which is shown to be a risk factor for UTI. A significant difference was observed in the culture growth of symptomatic males with BPH. CONCLUSION: In patients with urolithiasis, characteristics such as age, sex, blockage, multiple stone locations, and stone type (like staghorn stones) may be separate causes of UTIs. The most prevalent bacteria in UTIs in urolithiasis patients are gram-negative bacilli.